The Narrehans way of life a case study - Clerigo, Angelico B.
This research entitled "The Narrehans Way of Life" is a case study of the residents of the Narra Residence Halls. Their ways and topics of interaction, groups, norms were observed. Its influences on the their activities and traditions were observed and analyzed. The study used the interview guide as its major research instrument. Moreover, the diary was also utilized to substantiate data gathered through interviews. The researcher acted as a participant-observer. The typical case sampling under the purposeful sampling technique was used in getting the informants. Twenty informants were interviewed which gave enough data needed in this research. The findings of this research revealed that there is a strong bond existing among the Narrehans. Due to this fact, they sometimes decide on issues or problems based on their norms and beliefs instead of basing it on their experiences. These Norms and beliefs of Narrehans are passed on to every newcomer in the dormitory as they integrate with the old residents. Although at first, the newcomers are not as cooperative during their first days as Narrehans, they eventually absorb the culture of the residents. The study also revealed the strong and cohesive bond linking the NArrehans due to their constant interaction with each other. Finally, the study also revealed that in Narra, no matter what fraternity, province, organization, or religion a resident belongs there is no doubt that he would still be accepted by the old residents as long as he interacts and participate in their activities. They exist as one big and happy family.